A identidade do empreendedor social - Silva, Daniel Branchini da (2008)
The word entrepreneur, which comes from the French entrepreneur, means the one that takes in hands , and it was originally coined by economists such as Jean-Baptiste Say around 1800 to describe the individual that transfers economic resources from a sector of lower productivity to a higher and more profitable one. Later, in the 20th Century, Joseph Schumpeter adds the perspective of innovation as an essential feature, showing that the entrepreneur is the one who promotes a true destruction of the economic order by the introduction of new products and services. Such background reveals how much the word entrepreneur still preserves these features even today, for now it is being used to describe somebody who identifies opportunities, takes risks and makes things happen. In the last three decades, in a context marked by the State s social welfare bankruptcy and by the strengthening of the companies, the word social entrepreneur has appeared to outline the action of a specific type of entrepreneur who works in favor of the collectivity, searching for innovative solutions to emergent demands in areas such as education, health, environment, job and income generation, advocacy and other similar causes, aiming to promote systemic social changes in a sustainable perspective. Therefore, the objective of this research was to investigate the identity of this social entrepreneur, considering his historical roots, ideals and achievements in order to find out if there was an effective emancipation movement towards a post-conventional identity on his part. Thus, seven half-controlled interviews were carried out with individuals formally recognized as social entrepreneurs, whose life histories revealed that most of them continue playing the conventional role labeled by society, but that some have already been anticipating a movement that could indicate a new role to arise soon. Amongst the newly identified characters, one of them seems more like a regulating agent , whose cause involves the normatization of the system, and the other one seems like an emancipatory activist , whose cause is to give voice to the population segments that are ignored by society, stimulating the community itself to obtain its own emancipation